City profile: Suzhou - a Chinese city under transformation. (April 2015) - Wang, Lei; Shen, Jianfa; Chung, Calvin King Lam
Highlights: Suzhou, as an ancient city, shows some differences from other documented Chinese cities in its development trajectory towards modernization and urbanization. This profile primarily focuses on the city proper of Suzhou, while also discusses the whole municipality when relevant. It firstly introduces the city's historical development, followed by a detailed discussion on the socio-spatial transformation since China's open door policy in 1978. Then, the role of spatial planning in urban development and ancient quarter conservation is also investigated. Some remaining issues and challenges are discussed in the last part. Abstract: Suzhou is located at the center of lower Yangtze River Delta (YRD). With a history of more than 2500 years, it has been transformed from a famous national commercial city in history to a vanguard of globalization known as a modern industrial city in contemporary China. It was not until the reform and opening in 1978 that the traditional spatial structure of the city was jeopardized. It has become an industrial base of Shanghai and relied on foreign direct investment and foreign trade remarkably through a new industrialization path of constructing development zones at various levels. Paralleling economic growth, it has exhausted massive agricultural land and caused rampant urban sprawl because spatial planning was not effective in development control. However, spatial planning does play an important role in the conservation of the ancient quarter which made Suzhou another model in the country. Lastly, some issues and challenges ahead in planning and governance are also discussed.